2009
DOI: 10.1073/pnas.0909265106
|View full text |Cite
|
Sign up to set email alerts
|

Telomere shortening relaxes X chromosome inactivation and forces global transcriptome alterations

Abstract: Telomeres are heterochromatic structures at chromosome ends essential for chromosomal stability. Telomere shortening and the accumulation of dysfunctional telomeres are associated with organismal aging. Using telomerase-deficient TRF2-overexpressing mice (K5TRF2/Terc ؊/؊ ) as a model for accelerated aging, we show that telomere shortening is paralleled by a gradual deregulation of the mammalian transcriptome leading to cumulative changes in a defined set of genes, including up-regulation of the mTOR and Akt su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Interestingly, these changes, viz. chromosome instability and altered gene expression, can result from disruption of telomeric complexes (22,23). Our observations that AR interacts with telomeric proteins (Figs.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, these changes, viz. chromosome instability and altered gene expression, can result from disruption of telomeric complexes (22,23). Our observations that AR interacts with telomeric proteins (Figs.…”
Section: Discussionmentioning
confidence: 83%
“…Several biological processes as well as cellular stresses have been described to infl uence TERRA levels and their nuclear localization and accumulation including the telomeric chromatin stage, telomere length, heat shock, exogenously infl icted DNA damage, as well as ontogenesis and cancer 6,8,32 (reviewed in Schoeft ner and Blasco 9 ). However, the TERRA-bound factors controlling all of these processes remain largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It is also known that gradual reduction in the telomere length associated to aging is linked to global deregulation of the transcriptome and loss of maintenance of epigenetic silencing mechanisms. 18 In line with extra-telomeric roles for shelterin proteins, Taz1, the fission yeast ortholog of mammalian TRF1 and TRF2, is also involved in telomere protection and recruitment of Rap1 to telomeres 19,20 and was recently described to bind to the internal telomeric repeats and play an essential role in the "replication timing control" (RTC), with about half of late origins and almost all origins in subtelomeric regions being regulated by the Taz1-mediated mechanism. 21 In agreement with this, a recent study reported restricted abilities of TRF1 and TRF2 proteins in binding extratelomeric sites of the genome in human tumor cell lines, most of them ITSs.…”
Section: Introductionmentioning
confidence: 99%